Digital Transformation of Supplier Management in Manufacturing: From Manual Processes to Cloud-Powered Collaboration - Hari Krishna Bethanaboina (International Journal of Computational and Experimental Science and Engineering, 2026)
Contemporary supplier relationship management transformation signifies a pivotal advancement in manufacturing operations, confronting persistent obstacles in procurement efficacy, compliance oversight, and partnership collaboration. This article investigates cloud-based supplier collaboration platform deployment within the mining and building materials manufacturing domain, wherein enterprises administer vast supplier networks whilst managing intricate compliance mandates and operational limitations. Conventional manual methodologies encompassing documentation, spreadsheets, and dispersed communication mechanisms have chronically yielded protracted cycle durations, irregular data integrity, and constrained transparency throughout procurement divisions. The investigation scrutinizes how a prominent manufacturing enterprise revolutionized supplier management practices via integrated cloud technologies, intelligence-driven verification frameworks, and mechanized workflow structures. The inquiry evaluates deployment methodology, technological framework, and consequential organizational ramifications of this transformation endeavor. Discoveries reveal considerable enhancements in operational productivity, compliance execution, and supplier relationship caliber subsequent to platform adoption. The evaluation augments comprehension of how manufacturing enterprises can harness digital capabilities to strengthen supplier collaboration, diminish operational vulnerabilities, and establish resilient supply chain alliances. The article culminates in exploring wider ramifications for procurement transformation and delineating trajectories for sustainable digital supplier management practices within complex industrial settings.